Synergistic activities of 4-arylcoumarins against phytopathogenic fungi - Thongchai Taechowisan (2018)
Different extracts of Streptomyces aureofaciens CMUAc130 culture were studied as potential antifungal agents for selected phytopathogenic fungi. In a serial agar dilution method, crude ethyl acetate and 10% methanol in ethyl acetate extracts exhibited fungistatic activity against Aspergillus flavus, Colletotrichum musae, Fusarium oxysporum, Pythium ultimum, Rhizoctonia solani and Sclerotium rolfsii. Both ethyl acetate extract and 10% methanol in ethyl acetate extract were highly effective on all tested fungi, with Minimum Inhibitory Concentration (MIC) values ranging from 0.25 to 50 and 10 to 100 mg mL-1, respectively. The major active ingredients from those extracts were purified by silica gel column chromatography and identified to be 5, 7, 4′-trimethoxy-4-phenylcoumarin (1), 4′-hydroxy-5,7-dimethoxy-4- phenylcoumarin (2), 3′-Hydroxy-5,7,4′-trimethoxy-4-phenylcoumarin (3), 5,7,3′,4′-Tetramethoxy-4-phenylcoumarin (4) and 4′-hydroxy-5,7,3′-trimethoxy-4-phenylcoumarin (5) by NMR and mass spectral data, respectively. Five compounds (1 to 5) had activity against P. oxysporum with MICs of 0.30, 1.00, 0.40, 10.00 and 20.00 mg mL-1, respectively. Compounds 1, 2 and 3 also showed a synergistic effect when combined in different concentrations, displaying four times less concentration to reach complete inhibition in the growth of F. oxysporum. © 2008 Academic Journals Inc.